Interaction potential of etravirine with drug transporters assessed in vitro - Zembruski, Nadine Cécile Luise; Haefeli, Walter E.; Weiß, Johanna (Antimicrobial agents and chemotherapy, 2011)
Etravirine is a novel nonnucleoside reverse transcriptase inhibitor (NNRTI) for the treatment of HIV-1 infections. ABC transporters potentially mediate clinically relevant drug-drug interactions. We assessed substrate characteristics and the inhibitory and inductive potential of etravirine on ABC transporters. Etravirine did not inhibit P-gp/ABCB1 and was not transported by the tested ABC transporters but was a potent inhibitor of BCRP/ABCG2. Etravirine induced several ABC transporters, especially BCRP/ABCG2. These data demonstrate that etravirine has the potential for drug-drug interactions by modulation of expression and function of several ABC transporters.
Gesehen am 22.12.2022